De novo late postpartum preeclampsia: a case report with review of literature - Hota, Basanta Manjari; Anusha, N. S. Sai; Sneha, Guguloth; Devisri, Yallamandala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
De Novo late postpartum preeclampsia is defined by many authors as new onset postpartum hypertension of ≥140/90 mmHg with features of organ system malfunctioning during 48 hours to six weeks of delivery following a normotensive pregnancy and labor. Though a lesser studied condition it is responsible for more number and increased severity of maternal morbidity, mortality, and cause of post-delivery hospital admission. Its exact cause is not yet clearly defined. The incidence is 0.3-27% as noted by many authors. Patients usually present on day 7-10 with severe headaches, neurological symptoms like visual disturbances; symptoms of other organ involvement, and high blood pressure. High suspicion leads to diagnosis. Primary investigations include that for preeclampsia. The principle of management is the reduction of blood pressure, prophylactic anticonvulsants, and diuretic is considered if there are features of fluid overload. She needs constant monitoring. Post delivery women, after discharge, do not avail of home blood pressure monitoring and even the symptoms, to start with are treated with over-the-counter medication. This leads to worsening of the condition. Our patient, a primipara reported to this hospital on the 38th day of normal vaginal delivery following a normotensive pregnancy and delivery, with features of preeclampsia. The aim of publishing this case is for statistical records and create awareness of the condition. Every postpartum woman on discharge from the hospital following a normotensive pregnancy and delivery must be counseled on the significance of home BP monitoring and must consult an obstetrician on developing any new symptoms.